Status and future pathways of resin tapping in Nepal: Appeal for special attention (Nepal Journal of Environmental Science, 2021)
Resin tapping was pioneered five decades ago since the Laxmi Tapping industry started tapping in western Nepal in 1973. Resin tapping is acknowledged as a cost-effective, viable, and adjuvant source of income for rural people with the potentiality for payment for ecosystem services (PES) outside the resin tapping period. This paper explores the SWOT analysis of resin tapping and future pathways to improve this enterprise in Nepal. The systematic and comprehensive literature search was conducted in Google Scholar, ScienceDirect, PubMed, and Scopus; and PRISMA flowchart summarizes the search strategy of the literature survey. SWOT analysis concludes that resin tapping has more strengths and opportunities, but this enterprise is currently under threat due to the shutting down of many resin enterprises with royalty hikes and no incentive. Poor tapping techniques lead to the depletion of pine resources in the long term, so the weakness of the rill method should be counteracted by the modern, cost-effective, more efficient borehole method practiced in many developed countries for resin production. Implementation of the proper policy framework, provision of incentives for enterprise, and sufficient research to create a knowledge base about resin tapping is an urgent need to minimize threats and pedal this enterprise in the right direction. We insist policymakers and stakeholders adopt the integrated forest-based enterprise approach for enabling environment in resin tapping and recommend nine promising value chain upgrading strategies as pragmatic endorsements to execute this enterprise in the long run.